2018
DOI: 10.1039/c8ce00617b
|View full text |Cite
|
Sign up to set email alerts
|

Disorder–order transitions in the perovskite metal–organic frameworks [(CH3)2NH2][M(HCOO)3] at high pressure

Abstract: Compression of dimethylammonium metal formates results in distorted metal formate frameworks and loss of dynamic disorder of dimethylammonium simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
65
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 65 publications
10
65
2
Order By: Relevance
“…The high-pressure effect on perovskite-like MOFs has been studied previously using Raman spectroscopy and X-ray diffraction for the DMAM II family (M II =Cd, 25 Mg, 25 Mn, 26,27 Fe 27 and Cu 27 ). Raman spectroscopy showed the presence of three phase transitions for DMAMg and DMAMn at 2.2 GPa, 4.0 GPa, and 5.6 GPa as well as at 2.1 GPa, 4.1 GPa, and 6.7 GPa, respectively, while only two phase transitions were found for DMACd, in the 1.2-2.0 GPa range and at 3.6 GPa.…”
Section: Pressure-dependent Raman Spectra Of Dmanacrmentioning
confidence: 99%
See 3 more Smart Citations
“…The high-pressure effect on perovskite-like MOFs has been studied previously using Raman spectroscopy and X-ray diffraction for the DMAM II family (M II =Cd, 25 Mg, 25 Mn, 26,27 Fe 27 and Cu 27 ). Raman spectroscopy showed the presence of three phase transitions for DMAMg and DMAMn at 2.2 GPa, 4.0 GPa, and 5.6 GPa as well as at 2.1 GPa, 4.1 GPa, and 6.7 GPa, respectively, while only two phase transitions were found for DMACd, in the 1.2-2.0 GPa range and at 3.6 GPa.…”
Section: Pressure-dependent Raman Spectra Of Dmanacrmentioning
confidence: 99%
“…25,26 The high-pressure X-ray diffraction studies only indicated the presence of one phase transition for DMAMn, in the 5.5-5.6 GPa range resulting from the transformation from ambient-pressure trigonal 3 to triclinic 1 symmetry. 27 The absence of the remaining two transitions was explained by their character, i.e. it was assumed that they result from the change of local symmetry, 27 which would be better visible using vibrational methods.…”
Section: Pressure-dependent Raman Spectra Of Dmanacrmentioning
confidence: 99%
See 2 more Smart Citations
“…[(CH 3 ) 2 NH 2 ]MnIJH 2 POO) 3 (ref. 41) and the triclinic high-pressure phase of [(CH 3 ) 2 NH 2 ]FeIJHCOO)3 ,42 yet are normally very weak. As the concept of "rigid units" is less valid in very distorted structures with low symmetry, this approach is perhaps less meaningful for such compounds.…”
mentioning
confidence: 99%